(untitled) (Journal of Pharmaceutical Negative Results, 2022)
Rheumatoid arthritis (RA) is a systemic, chronic, autoimmune inflammatory disease affecting the joints of an individual hindering the quality of life. To treat RA, usually non-steroidal anti-inflammatory drugs, steroids, glucocorticoids are used. In the recent past, it has been observed that extracts and compounds derived from plants are effective in treating RA. Also, compounds that bind to MMP2, MMP9 can be potential drug targets for further study. Aerva lanata is a plant constituting diverse phytochemicals and a rich source for Canthin-6-one and ß-carboline alkaloids. This work focusses on binding of the compounds Canthin-6-one, 10-hydroxy-canthin-6-one, 9-Methoxycanthin-6-one and 7-methoxy-beta-carboline-1-propionic acid present in Aerva lanata with MMP2 and MMP9. From bioactivity spectrum, it is noticed that these molecules are biologically active suggesting further studies to be carried out for exploring potential drug activity. Bioactivity score, drug likeness character was assessed in silico. Binding affinity score of Canthin-6-one alkaloids with MMP2 and MMP9 obtained through molecular docking revealed that these molecules are potential drug targets for treating RA.